Digital readiness of Islamic rural banks in Indonesia: Lesson from the COVID-19 pandemic - Dety Nurfadilah; Sudarmawan Samidi; Wiwiek M Daryanto (Cogent Business & Management, 2023)
The goal of this research is to investigate how various variables, including ease of use, usefulness, and social influence, competencies affect a specific phenomenon, and COVID-19 on digital readiness and examine the role of attitude as mediating variables. This study used a quantitative research method that gathers the data through questionnaires to employees at Islamic rural banks in Java Islands, Indonesia. Three hundred and seventy-eight respondents from Java and outside Java islands across Indonesia were collected and the data were analyzed by SEM-PLS. The result shows that perceived ease of use and perceived usefulness drive the attitude of employee at Islamic rural banks which also affect their readiness for digital transformation. Further, COVID-19 and competency also found to have positive effect on digital readiness. The originality of this study is to provide new perspective that COVID-19 drive the emergence of digital transformation in Islamic rural banks. Moreover, by analyzing the attitudes and competencies of employee and management, this study fills the gap to uncover the critical factors that shape the outcome of digital transformation in Islamic rural banks in Indonesia.
Keywords: 650; covid-19 pandemic; digital readiness; employee's competency; Islamic rural banks; perception